The urological anomalies associated with anorectal malformations - Hmed Al-kawaz, Shatha A.; Lattuf Al-Rudaini, Maha A.; Jaafer, Thura K. (Journal of the Faculty of Medicine Baghdad, 2013)
Background: Urological anomalies are frequently associated with anorectal malformations which are a common source of significant morbidity.Objective: Is to evaluate the incidence and nature of the urological anomalies with patients of anorectal malformations (ARM).Patients & methods: The data  from  95 patients with ARM were studied from January 2009 to January 2012 in this cross-sectional study. All patients underwent sonography of urinary tract. Voiding cystourethrogram (VCUG) was done in patient with abnormal sonography & to all male patients with ARM who underwent colostomy. Other imaging studies were done in selected cases.Results: Males significantly constitute the majority 64/95 (67.4%) of ARM cases, while females constitute 31/95 (32.6%) of patients, male to female ratio is 2:1. High type anomaly significantly constitutes the majority of the patients 79/95 (83.2%)  in both genders. Urologic malformations were found in 24/95 (25.3%) patients with a significantly high frequency in males 21/64 (32.8%) while 3 of them were females 3/31 (9.7%).  Urological anomalies occur more with high type ARM (27%) versus (12%) in low type ARM. Vesicoureteral reflux (VUR), renal agenesis, and hydronephrosis were the most common urologic anomalies respectively.Conclusions: The high incidence of associated urogenital anomalies necessitates a careful investigation of all patients with ARM and continued long term follow up of these patients is mandatory to avoid deterioration of renal function in future.